PERAN TEMAN SEBAYA TERHADAP PERILAKU ASERTIF MAHASISWA AS-SYUKRIYYAH - Luluk, Laili Riskiyah; Wiantina, Nur Azmi; Siregar, Fitriana (JIEGC Journal of Islamic Education Guidance and Counselling, 2025)
ABSTRACT This study explores the role of peer groups in shaping assertive behavior among university students, with particular attention to the dynamics of social interaction within higher education settings. A qualitative approach using a case study method was employed at As Syukriyyah Campus, Tangerang, in June 2025. The participant was purposively selected—an active student in social contexts but exhibiting a low level of assertiveness. Data were gathered through in-depth interviews, observations, and document analysis. The data analysis was guided by the Miles and Huberman model, involving data reduction, data display, and conclusion drawing. The findings demonstrate that peer groups significantly contribute to the development of assertive behavior. Supportive, egalitarian, and empathetic interactions enable students to express opinions confidently, uphold personal boundaries, and engage in constructive interpersonal communication. Additionally, peers function as sources of emotional support and serve as behavioral role models, reinforcing students’ self-confidence and social competence. These results highlight that a positive peer environment is a key factor in promoting the formation of assertive character in university students.